Developing A Simple Teaching Aid on The Human Circulatory System: Validity Evidence From Expert Judgement - Ibadur Rahman; Dios Sarkity; Nevrita Nevrita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
Education is a comprehensive process that encompasses guidance, development, regulation, supervision, and the transmission of values from educators to learners. Learning media refer to any tools or resources employed to convey instructional messages in ways that stimulate students’ thinking, emotions, attention, and motivation, thereby facilitating a structured, goal-directed, and well-managed learning experience. This study aims to develop a simple teaching aid on the human circulatory system for eleventh-grade students using readily available materials, while ensuring its validity as an instructional medium. The research adopted three of the five stages of the ADDIE development model—Analysis, Design, and Development. The study did not proceed to the implementation phase; instead, it focused on the development stage, particularly validity testing. Data were collected through interviews, classroom observations, and questionnaire distribution. The analysis combined quantitative methods, involving percentage score calculations, with qualitative evaluation derived from validators’ feedback and recommendations. The findings indicate that students require visually engaging instructional media that are practical to use and aligned with the expectations of the Merdeka Curriculum. In conclusion, the design phase produced a prototype teaching aid that is considered appropriate for use in biology instruction, demonstrating a very high level of validity and strong potential to enhance the learning process.